Investigation of heat transfer of wall with and without using phase change material. (2020) - Arunkumar, D.; Ramu, M.; Murugan, R.; Kannan, S.; Arun, S.; Baskar, Sanjeevi
Abstract: As part of reducing energy use for building application like cooling and heating, the phase change material (PCM) plays a vital role, it be incorporated into building structure and materials in an effective manner. In this research concentrated to find the effect of heat transfer of PCM filled hollow block (wall) and unfilled one, tested in a natural climatic condition of Chennai. In this regard Organic Material OM29 PCM is chosen based on average temperature persists on the selected location, it acts as thermal barrier also minimize the heat entering to the room. Heat gain of the building wall is respective to seasonal variations based on that the selected OM29 is to be effective only where the clear sunny days, over the period the PCM performance is to be optimized. The result shows that temperature drop of 5.7% and heat gain reduction of 33% are observed across the dimensions of the hollow block in the indoor surface, the temperature at various points in a surface is similar. The results showed the selected PCM have great influence in reduction of heat transmission from external face to internal face in hot climates, however for a moderate climate, the solar intensity differs from day to day so cooling transmission loads it varies, so employability of PCM influenced by ambient factors. The numerical simulations were performed thus the results are validated with experimental, in the incorporated PCM was effective in the months of April to July.